Integration-free induced pluripotent stem cells from three endangered Southeast Asian non-human primate species - Qiuye Bao; Nicole Liling Tay; Christina Yingyan Lim; Delia Hwee Hoon Chua; Su Keyau Kee; Mahesh Choolani; Yuin-Han Loh; Soon Chye Ng; Chou Chai (Scientific Reports, 2024)
Abstract Advanced molecular and cellular technologies provide promising tools for wildlife and biodiversity conservation. Induced pluripotent stem cell (iPSC) technology offers an easily accessible and infinite source of pluripotent stem cells, and have been derived from many threatened wildlife species. This paper describes the first successful integration-free reprogramming of adult somatic cells to iPSCs, and their differentiation, from three endangered Southeast Asian primates: the Celebes Crested Macaque (Macaca nigra), the Lar Gibbon (Hylobates lar), and the Siamang (Symphalangus syndactylus). iPSCs were also generated from the Proboscis Monkey (Nasalis larvatus). Differences in mechanisms could elicit new discoveries regarding primate evolution and development. iPSCs from endangered species provides a safety net in conservation efforts and allows for sustainable sampling for research and conservation, all while providing a platform for the development of further in vitro models of disease.